Flexible ultraviolet detector with robust ZnO nanoparticle nanoassemblies on catechol‐functionalized polysiloxane nanofilms. Issue 37 (30th April 2021) - Liu, Yida; Zhu, Huie; Watanabe, Akira; Yamamoto, Shunsuke; Miyashita, Tokuji; Mitsuishi, Masaya
Abstract: As a result of the vast Young's moduli difference between an inorganic semiconducting channel and flexible substrates, flexible optoelectronic devices readily lose their functionality through material delamination and local fracturing, which lead to short‐circuiting of devices. For this study, we synthesized a catechol‐containing polysiloxane (CFPS) adhesive and applied it to ZnO nanoparticle (NP) assembly on plastic substrates for flexible UV detector applications. The 30 nm thick CFPS adhesive can anchor 70 nm thick ZnO NPs strongly through a coordination bond, thereby forming an ultra‐stable ZnO NP channel layer. A peeling test of ZnO NP layer was conducted using transparent tape (Scotch®; 3 M Inc.). The ZnO NPs were firmly immobilized, reflecting the outstanding mechanical stability of CFPS adhesives. A UV detector also exhibited stable photo‐response performance even after a thousand iterations of bending with 3 mm curvature radii. The result indicates the polycyclosiloxane‐based flexible device as promising for wearable detector applications. Abstract :